Korea's metal resources recycling research project – valuable recycling. Issue 1 (2nd January 2019) - Cho, Bong-Gyoo; Cho, Young-Ju; Lee, Jae-chun; Yoo, Kyoungkeun
ABSTRACT: South Korea imports 99% of its mineral metal resources, so it is important to recover valuable metals from metal-containing waste for sustainable domestic industry development. The Korean government launched a 10-year recycling research project, 'Valuable Recycling', in May 2011 with 180 million funding (150 million from the government). The objectives of the project were to develop highly efficient technologies that improve the resource recycling ratio and quality of life, and meet international environmental regulations for enhancing the competitiveness of domestic industries. The project includes 26 sub-projects classified into four categories: electrical & electronics, automotive, metals & inorganics, and organics. The main research achievements and recycling processes are presented in this article.